How small is the big problem? Small microplastics <300 μm abundant in marine surface waters of the Great Barrier Reef Marine Park. (November 2022) - Carbery, Maddison; Herb, Frithjof; Reynes, Julien; Pham, Christopher K.; Fong, Wye-Khay; Lehner, Roman
Abstract: Particle size plays an important role in determining the behaviour, fate and effects of microplastics (MPs), yet little is known about MPs <300 μm in aquatic environments. Therefore, we performed the first assessment of MPs in marine surface waters around the Whitsunday Islands region of the Great Barrier Reef Marine Park, Australia, to test for the presence of small MPs (50–300 μm) in-situ . Using a modified manta net, we demonstrate that MPs were present in all marine surface water samples, with a mean sea surface concentration of 0.23 ± 0.03 particles m −3 . Microplastics were mainly blue, clear and black fibres and fragments, consisting of polyethylene terephthalate, high-density polyethylene and polypropylene plastic polymers. Tourism and marine recreation were considered the major contributing sources of MPs to surface waters around the Whitsunday Islands. Between 10 and 124 times the number of MPs exist in the 50 μm–300 μm size class, compared with the 1 mm–5 mm size range. This finding indicates that the global abundance of small MPs in marine surface waters is grossly underestimated and warrants further investigation. Research into the occurrence, characteristics and environmental fate of MPs <300 μm is needed to improve our understanding of the cumulative threats facing valuable ecosystems due to this smaller, potentially more hazardous size class. Graphical abstract: Unlabelled Image Highlights: First study of MPs in surface waters of the Whitsunday Islands region Microplastics 50 μm–5 mm widespread in surface water samples At least 10–124 times more particles exist in the 50 μm–300 μm size range. Predominantly fibres and fragments consisting of PET, HDPE and PP Tourism and marine recreation were likely contributing sources.